A proposed course guide in social studies II geared to the new social studies - Llobrera, Nina Josefina Dakanay 1942- (s.n.], 1972)
In the University of the Philippines High School, the curriculum has already been revised along the principles of curricular reform development. The new curriculum was instituted in the school year 1971-1972. Improvements on the different areas of this revised curriculum are constantly being undertaken. It is along these developments that this study was made.